Phytochemical evaluation and in vitro antioxidant and photo-protective capacity of Calendula officinalis L. leaves - V.C.K.N. DEUSCHLE; R.A.N. DEUSCHLE; M. PIANA; A.A. BOLIGON; M.R.B. BORTOLUZZI; V. DAL PRÁ; C.B. DOLWISCH; F.O. LIMA; L.M. CARVALHO; M.L. ATHAYDE (Universidade Estadual Paulista, 2015)
ABSTRACT The plant Calendula officinalis L. is widely applied due to its medicinal properties, which are mainly dermatological and ornamental. The goal of this study is to assess the phytochemical components in a hydroethanolic extract (HECO) from the leaves of Calendula officinalis L. using UV-VIS spectrophotometry and thin layer chromatography (TLC), as well as to identify and quantify the components related to its antioxidant capacity employing high performance liquid chromatographic (HPLC). The antioxidant capacity evaluation was performed using the DPPH method for superoxide and hydroxyl radicals. The photo-protective capacity was evaluated by UVspectrophotometry in order to determine the in vitro Sun Protection Factor(SPF). The results show the plant's strong antioxidant activity (DPPH and hydroxyl methods), which we believe to be related to the presence of flavonoids (24.67 mg/g), polyphenols (33.90 mg/g), condensed tannins (27.30 mg/g), and the amount of rutin (37.25 mg/g), and quercetin (6.09 mg/g) found during the study. The HECO presented a good antioxidant capacity, most likely due to the polyphenols, flavonoids, and tannins in its contents. However, the obtained SPF of 1.89 ± 0.05 does not allow the plant to be classified as a stand-alone sunscreen, and more studies are needed in order to test its ability to enhance sunscreens in existing cosmetic formulations.